Diagnostic accuracy and implementation of computed tomography angiography for gastrointestinal hemorrhage according to clinical severity - Choi, Yoo Jin; Kim, Kyung Su; Suh, Gil Joon; Kwon, Woon Yong (Clinical and experimental emergency medicine, 2016)
This study compared the diagnostic accuracy of computed tomography (CT) angiography in patients with various severities of gastrointestinal hemorrhage (GIH). We retrospectively enrolled adult patients (n=262) with GIH who had undergone CT angiography from January 2012 to December 2013. Age, sex, comorbidities, presenting symptoms, initial vital signs, laboratory results, transfusion volume, emergency department disposition, and hospital mortality were abstracted from patient records. CT angiography findings were reviewed and compared to reference standards consisting of endoscopy, conventional angiography, bleeding scan, capsule endoscopy, and surgery, either alone or in combination. Clinical severity was stratified according to the number of packed red blood cell units transfused during the first two days: the first quartile was categorized as mild severity, while the second and third quartiles were categorized as moderate severity. The fourth quartile was categorized as severe. Patients were categorized into the mild (n=75, 28.6%), moderate (n=139, 53.1%), and severe (n=48, 18.3%) groups. The mean number of transfused packed red blood cell units was 0, 3, and 9.6 in the mild, moderate, and severe groups, respectively. The overall sensitivity, specificity, positive predictive value, and negative predictive value of CT angiography were 73.8%, 94.0%, 97.3%, and 55.3%, respectively. The area under the receiver operating characteristics curve for the diagnostic performance of CT angiography was 0.780, 0.841, and 0.930 in the mild, moderate, and severe groups, respectively, which significantly differed among groups (P=0.006). The diagnostic accuracy of CT angiography is better in patients with more severe GIH.